A molecular dynamics study of cellulose inclusion complexes in NaOH/urea aqueous solution. (1st April 2018) - Liu, Gang; Sun, Heng; Liu, Guokui; Zhang, Heng; Yuan, Shiling; Zhu, Qingzeng
Graphical abstract: Highlights: The MD simulation was used to study the cellulose ICs in NaOH–urea aqueous system. All components in cellulose/NaOH/urea aqueous solution were combined in one model. Atomic level scrutiny of spatial structure of cellulose ICs was achieved. The hydrogen bond lifetime was quantitatively estimated in cellulose ICs. Water–water angles distribution in cellulose inclusion complexes was well studied. Abstract: We investigated the dissolution state of cellulose in NaOH/urea aqueous solution using molecular dynamics simulations. All the components, including cellulose, NaOH, urea and H2 O were combined into one simulation. A clear and detailed description for the formation of cellulose inclusion complexes has been stated. The simulation results showed that the cellulose inclusion complexes exhibited anisotropic properties. In this system, the sodium ions and hydroxide ions located at the regions of hydroxyl and hydroxymethyl groups in cellulose molecules. However, the urea molecules occupied the faces of the hydrophobic pyranose rings. The hydrogen-bonding configuration and lifetime of hydrogen bonds in cellulose inclusion complexes were also systematically characterized. The spatial structure of inclusion complexes, the hydrogen-bonding interaction between cellulose and solvent molecules, the diffusive property of solvent molecules and the distribution of water–water angles in cellulose inclusion complexes were discussed in details. The NaOH, urea and H2 O molecules surrounding the cellulose chain within radial distance 0.35 nm have smaller diffusion coefficients than those in bulk state. The water–water angles provide a quantitative estimate of hydrophobic effect of cellulose.